(untitled) (Revista NUPEART, 2023)
This article starts from the crossroads and urgencies invol- ved in the process of teaching and creating the scenic show entitled Sagrada Malandragem, inspired by Zé Pelintra and the sacred trickery of an Afro-religious matrix. Put together with students from technical courses at the School of Theater and Dance at the Federal University of Pará, the play triggers the analysis of the teaching and scenic creation processes develo- ped by the directors and guided by an anti-racist perspective. The pedagogies that permeate the production of the play seek strategies of education through diversity and breaking with oppressive paradigms of raciality, evident both from the point of view of the staging and the scene music.